Development of a Simple and Low-cost Smartphone Gimbal with MPU-6050 Sensor - Arif Ainur Rafiq; Wahid Nur Rohman; Sugeng Dwi Riyanto (Journal of Robotics and Control (JRC), 2020)
This paper discusses about design and development of gimbal smartphone, which are made to be simple and less money consuming by utilizing microcontroller and MPU 6050 sensor. Recently, the development of videography and image processing is inseparable from the rapid advance in smartphone technology. One of the most popular features is camera. Hand movements and shocks cause fewer maximum results. To improve the quality of camera captures and video, it is necessary to have a stabilizer for camera position.  Thus, it is expected that the outcomes of this paper are able to give contribution for cheap gimbal smartphone. Design and implementation of gimbal uses acrylic as the material, with 5 mm of thickness. This MPU 6050 sensor is optimized to detect sway in axis X, Y, and Z or roll, pitch, and yaw. Gyroscope and accelerometer provide input to the microcontroller, which will process for output on 3 servomotors that function to maintain the camera’s position at a specified set point. The results show that MPU 6050 sensor can response angle reading error of 1.34° of roll, 0.25° of pitch, and 0.78° of yaw. Error in maximum servomotor movement is 1.5°. Thus, it can be concluded that gimbal can work optimally with less money consuming as well as low error. It is expected that the next research will add other suitable and accurate control, that is, PID or fuzzy.